2022
DOI: 10.48185/jtls.v3i1.368
|View full text |Cite
|
Sign up to set email alerts
|

Language learning strategy preferences and levels of willingness to communicate by Iranian EFL learners

Abstract: The present study aims at investigating the relationship between Iranian EFL learners’ levels of willingness to communicate (WTC) and their preferences of language learning strategies.To achieve this goal, a quantitative study was carried out with 46 Iranian EFL learners majoring in English translation. The participants’WTC levels were determined through willingness to communicate (WTC) questionnaire developed by McCroskey and Richmond (2013). Oxford’s (1990) Strategy Inventory for Language Learners (SILL) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…The findings of this part of the study confirms the results by Yılmaz (2010) who found that compensation strategy is the most frequently used language learning strategy. The results, however, contradict the findings by Najafi and Dehghani (2022) that revealed metacognitive and cognitive strategies as the most frequent and compensation strategy as the least frequent strategies by EFL learners.…”
Section: Discussion On the Second Research Questioncontrasting
confidence: 98%
“…The findings of this part of the study confirms the results by Yılmaz (2010) who found that compensation strategy is the most frequently used language learning strategy. The results, however, contradict the findings by Najafi and Dehghani (2022) that revealed metacognitive and cognitive strategies as the most frequent and compensation strategy as the least frequent strategies by EFL learners.…”
Section: Discussion On the Second Research Questioncontrasting
confidence: 98%